Cellular and molecular mechanisms of hypoxia-inducible factor driven vascular remodeling - Hänze, Jörg; Weissmann, Norbert; Grimminger, Friedrich; Seeger, Werner; Rose, Frank (Thrombosis and Haemostasis, 2007)
Hypoxia-inducible factor (HIF) is an oxygen-dependent transcription factor that activates a diverse set of target genes, the products of which are involved in adaptive processes to hypoxia. Employing genetic manipulation of HIF expression, in-vivo and cellular studies have focused on HIF as a crucial factor affecting hypoxia-induced vascular remodeling.Vascular remodeling comprises processes which establish and improve blood vessel supply such as vasculogenesis, angiogenesis and arteriogenesis. These processes are observed during ontogenesis, tumor progression, ischemic disease or physical training. Furthermore, under hypoxic conditions, a pulmonary-specific type of vascular remodeling called pulmonary arterial remodeling occurs that is characterized by thickening of the vessel wall with a concomitant reduction in the vessel lumen area, thereby limiting blood flow.This response results in pulmonary hypertension with right ventricular hypertrophy, a lethal disease. In this review, we summarize and discuss mechanisms by which HIF interferes with the different vascular remodeling processes.
Keywords: Arteriogenesis; angiogenesis; vasculogenesis; hypoxia; pulmonary hypertension